Kualitas Tidur dan Tingkat Stres pada Populasi - Natasya Putri Syafei; Nathania Sekar Nuranindya; Rafika Shela Meka; Debi Miranda Sose; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
Sleep quality is an important factor that influences an individual's psychological condition, especially stress levels. Problems with poor quality sleep can trigger increased stress and reduce an individual's ability to carry out daily activities. This research aims to determine the relationship and influence of sleep quality on stress levels. The research method used is a quantitative approach with the Spearman correlation method. The research subjects consisted of 50 respondents. Data collection was carried out through sleep quality questionnaires and stress scales which were distributed online using Google Forms. Data analysis includes Spearman's correlation test, descriptive statistics and regression tests. The results of the Spearman correlation test show that there is a significant relationship between sleep quality and stress levels with a correlation coefficient value of r = 0.451 and a significance value of p < 0.001, which is included in the moderate relationship category. The results of descriptive statistics show an average value of sleep quality of 17.34 and stress level of 17.62. The regression test shows that sleep quality contributes 14.9% to stress levels and has a significant effect. This research concludes that quality sleep can be an effort to reduce stress.